Evaluation Of Construction Project Time And Cost Control Based On Earned Value And Crash Project Method - Mohammad Irfandio Kurniawan; Diah Ayu Restuti Wulandari; Julistyana Tistogondo (Neutron, 2021)
Project development and how to control time and costs in the construction project of a public junior high school 1 Surabaya. This research was conducted with the aim of knowing and comparing the amount of duration and cost after acceleration by using the alternative Earned Value Analysis. The case study in this research takes the construction project of a public junior high school 1 Surabaya which is located in Surabaya. The data needed in this study include the S curve, recapitulation of project cost calculations, a list of budget plans (RAB), and a list of unit wage prices for workers. The research method used is to design network planning, calculate the cost variance and variance schedule for each activity that changes due to changes in the duration of implementation, acceleration of work duration, and determination of the optimum cost and duration due to the application of the Earned Value Analysis method. For the calculation of the variance Schedule on week 34 shows a positive result of Rp. 109,550,470. For the calculation of the cost variance from week 34 shows - Rp. 2,488,159. For the calculation of Estimate at completion (EAC) on week 34 of Rp. 6,663,998,229. For the calculation of Estimate temporary schedule, the evaluation week 34 experienced a delay of 53 days from the original schedule. So the work completion time is 233 calendar days